Production of Euterpe precatoria Mart. seedlings in response to different dosages of nitrogen and potassium - Gude Butzke, Angelita; Silva de Brito, Rychaellen; de Carvalho Andrade Neto, Romeu; Maria Pereira Lunz, Aureny; da Silva Fiuza , Sergio; Almeida Andrade, Reginaldo (Comunicata Scientiae, 2023)
The success of açaí establishment as a monoculture is associated with the care regarding seedling quality and health. From this perspective, this study aimed to evaluate the influence of nitrogen and potassium to produce seedlings of Euterpe precatoria Mart. The experiment was set up in a randomized block design in a 5x5 factorial arrangement, with the first factor corresponding to nitrogen levels (0, 15, 30, 45, and 60 mg dm-3 of N) and the second factor consisting of the potassium levels (0, 40, 80, 120, and 160 mg dm-3 of K), aplit into 20, 40, and 40% of the total dosage. The following were evaluated 300 days after harvesting: seedling height, stem diameter, number of active leaves, dry root, shoot, and total mass, and the Dickson Quality Index. The data were subjected to univariate analysis and then to regression analysis. A significant effect was observed only for the N levels, with a positive linear response on all variables analyzed. Thus, the nitrogen levels influenced the growth and quality of E. precatoria seedlings 300 days after transplanting. Potassium fertilization for E. precatoria seedlings during the nursery phase was not responsive to any variable. In addition, there was no effect of the interaction between the N and K levels on the growth of E. precatoria seedlings 300 days after transplanting, and seedlings subjected to increasing nitrogen levels were responsive, showing good morphological attributes.